Respuesta :
Answer:
-8
Step-by-step explanation:
f(-4)= 3x+4
f(4)= 3(-4)+4
f(-4)=-12+4
f(-4)=-8
Answer:
f(-4) = -8
Step-by-step explanation:
Another way you can look at it is this way.
y = 3x+4; where x = -4. In this way, you just need to find what y is.
Since we are given x, all we have to do is replace x with it's numeric value (-4).
[tex]y = 3x+4;\\y=3(-4)+4\\y=-12+4\\y=-8[/tex]
Or in the same format they gave:
[tex]f(-4) = 3x+4\\f(-4) = 3(-4)+4\\f(-4) = -12 + 4\\f(-4) = -8[/tex]
In the format they gave, they said what is the function of -4.
f(-4) = -8